Wearable self‐tuning antenna for emergency rescue operations. Issue 2 (1st January 2016) - Baroni, Andrea; Nepa, Paolo; Rogier, Hendrik
Abstract : In this study, the design, hardware implementation and characterisation of a self‐tuning 406 MHz antenna of a Cospas‐Sarsat personal locator beacon are presented. The realised prototype is able to perform automatic tuning of the antenna under time‐varying environmental conditions due to human body movements and sea water proximity. The impedance tuning is performed by tracking the instantaneous value of the reflection coefficient and by modifying an appropriate impedance matching network according to a real‐time adaptive algorithm. A resilient default/backup software architecture has been designed to ensure that tuning guarantees a return loss higher than 10 dB for the personal locator beacon in most of impedance mismatching conditions.